Cerebellar pleomorphic xanthoastrocytoma - Raghavendra Harpanahalli; Bhaskar Suryanarayanan; Minakshi Bhardwaj; L.N. Gupta (Indian Journal of Neurosurgery)
Pleomorphic xanthoastrocytoma (PXA) is a relatively rare neoplasm predominantly occurring in the supratentorial compartment. Among the unusual locations, cerebellum is the most common with few cases reported in the spinal cord and retina. The infratentorial PXA has a female preponderance, occurs in the fourth decade of life and is composite in 2/3rd of the cases as compared to the supratentorial lesions. Gross total surgical excision is the goal, but is difficult due to the infiltration of the lesion into brainstem/upper cervical cord. Adjuvant radio/chemotherapy for recurrent/progressive/malignant forms have been, reported, but with variable results. This case is of a 25-year-old man who had a cerebellar PXA extending into the upper cervical cord that was sub-totally excised.